The Role of the Information System for Keeping Citizens in the Public Service Perspective in Bira Village, Bulukumba Regency - Umar Congge; Diljayanti Diljayanti; Muh Takdir (Program Pascasarjana Universitas Negeri Makassar, 2023)
The citizen guard information system (Si Jawara) through SimpelDesa is a public service innovation that is currently being implemented by the Bulukumba Regency Village government in providing public services, such as services, goods services, and administrative services as regulated by law. Therefore, the aim of this research is to describe the role of the citizen guard information system (Si Jawara) from a public service perspective. This type of research uses qualitative methods with a descriptive approach. Data sources consist of primary data and secondary data with data collection techniques used, namely observation, interviews, and documentation with reference to research objectives with research indicators regarding the function of public services, namely 1) public protection functions; 2) strategic infrastructure functions; 3) personal and local environmental functions. Data analysis techniques use an interactive analysis model with data analysis stages including data reduction; data presentation; validation test; and verification. The results of the research show that the citizen guard information system (Si Jawara) from a public service perspective in Bira Village, Bulukumba Regency, can be concluded that Si Jawara's innovation through SimpelDesa has a fairly good role in accommodating the needs of the village community, besides that the existence of SI Jawara helps and make it easier for the public to obtain public services, both services, goods and administrative services. Therefore, the innovation carried out by the Bira village government, Bulukumba Regency is part of efforts to improve or reform the bureaucracy and is expected to have a positive impact on neighboring villages